Policy of International Health Center (Medical Hub) (2017-2026) - Nongsai, Prakrubidika.Wasan; Sangthima, Watchara; Kaewoyaem, Wattana; Towmit, Sonchai (RATANABUTH JOURNAL, 2022)
The purpose of this academic paper is to study the implementation of the policy of the International Health Center and the guidelines for the preparation of medical and health services in the implementation of the International Health Center Policy. It found that Thailand has a policy to develop an international health center (2017 - 2026) Operational goals 1) Develop Thailand to be a service center for promoting health (Wellness Hub) 2) Develop Thailand to be a center of medical care. (Medical Service Hub) 3) Develop Thailand to be an academic and research service center (Academic Hub) and 4) Develop Thailand to be a center for medicines and health products (Product Hub) From the operations, it found that Thailand still has problems in the structure of the domestic economy. Health service infrastructure is insufficient to meet domestic needs. and the problem of health manpower shortages, etc. Therefore, from the public policy analysis to propose guidelines for the implementation of the policy to achieve its objectives, namely 1) develop medical personnel to have potential and suit their needs, 2) equality and clarity in resource allocation, and 3) determine the direction of Policy and Leadership Based on this review of strategic issues, indicators, and goals, it can lead to further development in the next period of time effectively.